Retrospective Comparison of Radiological and Clinical Outcomes of PLIF and TLIF Techniques in Patients Who Underwent Lumbar Spinal Posterior Stabilization. Issue 17 (April 2016) - Asil, Kiyasettin; Yaldiz, Can
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Degenerative disc disease and spinal stenosis lead to various symptoms. Degeneration of facet joints is added to this degenerative process with aging. Seventy-four patients who were admitted to the Spinal Column Outpatient Clinic of the Neurosurgery Department with a diagnosis of degenerative narrow spinal canal and lumbar spondylolisthesis between 2011 and 2013 and who underwent surgery were included in the study. Our study was conducted with 74 patients of whom 73.0% (n = 54) were female and 27.0% (n = 20) were male. Mean age was 54.86 ± 7.87 years (range 34–74). Although we did not detect a difference between the two surgical methods with regard to clinical improvement, transforaminal lumbar interbody fusion (TLIF) is preferred due to radiological advantages observed one year later, ease of application, and the development of fewer complications.